Self‐Assembly of Large‐Area 2D Polycrystalline Transition Metal Carbides for Hydrogen Electrocatalysis. Issue 50 (9th October 2018) - Zang, Xining; Chen, Wenshu; Zou, Xiaolong; Hohman, J. Nathan; Yang, Lujie; Li, Buxuan; Wei, Minsong; Zhu, Chenhui; Liang, Jiaming; Sanghadasa, Mohan; Gu, Jiajun; Lin, Liwei
Abstract: Low‐dimensional (0/1/2 dimension) transition metal carbides (TMCs) possess intriguing electrical, mechanical, and electrochemical properties, and they serve as convenient supports for transition metal catalysts. Large‐area single‐crystalline 2D TMC sheets are generally prepared by exfoliating MXene sheets from MAX phases. Here, a versatile bottom‐up method is reported for preparing ultrathin TMC sheets (≈10 nm in thickness and >100 μm in lateral size) with metal nanoparticle decoration. A gelatin hydrogel is employed as a scaffold to coordinate metal ions (Mo 5+, W 6+, Co 2+ ), resulting in ultrathin‐film morphologies of diverse TMC sheets. Carbonization of the scaffold at 600 °C presents a facile route to the corresponding MoC x, WC x, CoC x, and to metal‐rich hybrids (Mo2− x W x C and W/Mo2 C–Co). Among these materials, the Mo2 C–Co hybrid provides excellent hydrogen evolution reaction (HER) efficiency (Tafel slope of 39 mV dec −1 and 48 mVj = 10 mA cm‐2 in overpotential in 0.5m H2 SO4 ). Such performance makes Mo2 C–Co a viable noble‐metal‐free catalyst for the HER, and is competitive with the standard platinum on carbon support. This template‐assisted, self‐assembling, scalable, and low‐cost manufacturing process presents a new tactic to construct low‐dimensional TMCs with applications in various clean‐energy‐related fields. Abstract : Transition metal ions (Mo, Co, W) self‐organize within a gelatin template into a lamellar‐nanostructured soft material (metallohydrogel). Subsequent carbonization at moderate temperatures in a reducing atmosphere (600 °C) yields ultrathin (≈10 nm) and large (≈100 μm) 2D transition metal carbide sheets with high conductivity and rich active sites, which are ideal for the hydrogen evolution reaction (HER).